Vestibulo-Ocular Responses and Dynamic Visual Acuity During Horizontal Rotation and Translation - Ramaioli, Cecilia; Cuturi, Luigi F.; Ramat, Stefano; Lehnen, Nadine; MacNeilage, Paul R. (Frontiers in Neurology, 2019)
Dynamic visual acuity (DVA) provides an overall functional measure of visual stabilization performance that depends on the vestibulo-ocular reflex (VOR), but also on other processes, including catch-up saccades and likely visual motion processing. Capturing the efficiency of gaze stabilization against head movement as a whole, it is potentially valuable in the clinical context where assessment of overall patient performance provides an important indication of factors impacting patient participation and quality of life. DVA during head rotation (rDVA) has been assessed previously, but to our knowledge, DVA during horizontal translation (tDVA) has not been measured. tDVA can provide a valuable measure of how otolith, rather than canal, function impacts visual acuity. In addition, comparison of DVA during rotation and translation can shed light on whether common factors are limiting DVA performance in both cases. We therefore measured and compared DVA during both passive head rotations (head impulse test) and translations in the same set of healthy subjects (n = 7). In addition to DVA, we computed average VOR gain and retinal slip within and across subjects. We observed that during translation, VOR gain was reduced (VOR during rotation, mean±SD: position gain = 1.05±0.04, velocity gain = 0.97±0.07; VOR during translation, mean±SD: position gain = 0.21±0.08, velocity gain = 0.51±0.16), retinal slip was increased, and tDVA was worse than during rotation (average rDVA = 0.32±0.15 logMAR; average tDVA = 0.56±0.09 logMAR, p = 0.02). This suggests that reduced VOR gain leads to worse tDVA, as expected. We conclude with speculation about non-oculomotor factors that could vary across individuals and affect performance similarly during both rotation and translation.